Uji Aktivitas Antibakteri Sediaan Gel Hand Sanitizer Ekstrak Kulit Buah Jengkol (Archidendron pauciflorum (Benth.) Nielsen) terhadap Bakteri Escherichia coli: Antibacterial Activity Test for Gel Hand Sanitizer of Jengkol Rind (Archidendron pauciflorum (Benth.) Nielsen) Extract against Escherichia coli Bacteria - Rizka Ahyar Hidayati; Ary Kristijono; Afidatul Muadifah (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2021)
Escherichia coli is a bacteria that can cause diarrhea. The emergence of diarrhea is caused by a lack of public awareness in maintaining cleanliness, including hand hygiene. Along with the times, people prefer to use hand sanitizers that are more practical, easy to carry, and easy to use. However, most hand sanitizer preparations contain alcohol which has the potential to cause dryness and irritation if used continuously. Therefore, jengkol rind is used which contains flavonoid compounds, saponins, tannins, and anthraquinones which have antibacterial properties against Escherichia coli. The purpose of this study was to determine the antibacterial activity of the hand sanitizer gel of jengkol fruit peel extract against Escherichia coli using the disc diffusion method. The research method used was experimental. The jengkol rind samples were extracted using the maceration method with 70% ethanol. The positive control used was a hand sanitizer with chloroxylenol content and the negative control was a gel base without extract. Jengkol rind extract is made into preparations in concentrations of 5%, 10%, and 15%. The preparation was tested for physical stability for 28 days including organoleptic, pH, homogeneity, dispersibility, adhesion, protective power, and drying time. The results showed that the preparations with a concentration of 5%, 10%, and 15% jengkol fruit peel extract had an average inhibition zone of 7.00 ± 0.8165 mm, 13.00 ± 0.8165 mm, and 17.25 ± 0.95743 mm. Of the three formulations, the formulation with a concentration of 10% is the most effective concentration because a small concentration already has a strong inhibitory power category. The hand sanitizer gel of jengkol fruit peel extract fulfills the requirements for organoleptic tests, homogeneity, pH, spreadability, adhesion, and protection power and is stable in the 28-day storage period, but does not meet the requirements for drying time.